Effects of Far‐Infrared Emitting Ceramic Material Clothing on Recovery after Maximal Eccentric Exercise - Nunes, Renan Felipe Hartmann (J Hum Kinet, 2019)
The purpose of this study was to determine whether Far-Infrared Emitting Ceramic Materials worn as Bioceramic pants would improve neuromuscular performance, biochemical and perceptual markers in healthy individuals after maximal eccentric exercise. Twenty-two moderately active men were randomized into Bioceramic (n = 11) or Placebo (n = 11) groups. To induce muscle damage, three sets of 30 maximal isokinetic eccentric contractions of the quadriceps were performed at 60°·s(-1). Participants wore the bioceramic or placebo pants for 2 hours immediately following the protocol, and then again for 2 hours prior to each subsequent testing session at 24, 48 and 72 hours post. Plasma creatine kinase and lactate dehydrogenase activity, delayed-onset muscle soreness, perceived recovery status, and maximal voluntary contraction were measured pre-exercise and 2, 24, 48, and 72 hours post-exercise. Eccentric exercise induced muscle damage as evident in significant increases in delayed-onset muscle soreness at 24 - 72 hours (p < 0.05) and creatine kinase between Pre to 2, 24, 48 and 72 hours (p < 0.05). Despite the increased delayed-onset muscle soreness and creatine kinase values, no effect of Bioceramic was evident (p > 0.05). Furthermore, decreases in maximal voluntary contraction between Pre and immediately, 2, 24, 48 and 72 hours post (p < 0.05) were reported. However, the standardized difference was moderate lower for lactate dehydrogenase at 24 h (ES = 0.50), but higher at 48 h (ES = -0.58) in the Bioceramic compared to the Placebo group. Despite inducing muscle damage, the daily use of Far-Infrared Emitting Ceramic Materials clothing over 72 hours did not facilitate recovery after maximal eccentric exercise.